Moving Forward: A Discussion on the Revision of the ACRL Information Literacy Standards for Higher Education - Ellysa Stern Cahoy; Craig Gibson; Trudi E. Jacobson (Communications in Information Literacy, 2013)
Abstract: The first PA Forward Information Literacy Summit was held in State College at the Pennsylvania State University, University Park campus, on Wednesday, July 24, 2013. This summit brought together K-12 and academic librarians from Pennsylvania to discuss current issues in information literacy. This text is a transcript of a discussion between Ellysa Cahoy, past chair of the of the ACRL Information Literacy Competency Standards Committee, and the ACRL Information Literacy Competency Standards Review Task Force, and Craig Gibson and Trudi Jacobson who are currently co-chairs of the ACRL Information Literacy Standards Revision Task Force. This Task Force is charged with reviewing and revising the current ACRL Information Literacy Competency Standards for Higher Education, that were originally adopted by ACRL in 2000. This discussion was about the process by which the Standards came to be under review, some of the issues involved in the review, and the time line for the review and librarian feedback and comment on the process. The PowerPoint presentation which accompanied this discussion, as well as other documents mentioned during the presentation are attached to this transcript as supplemental files.